Effect of different sources of copper supplementation on performance, nutrient utilization, blood-biochemicals and plasma mineral status of growing Hariana heifers - VASWANI, SHALINI; KUMAR, VINOD; ROY, DEBASHIS; KUMAR, MUNEENDRA; KUSHWAHA, RAJU (The Indian Journal of Animal Sciences, 2018)
Twenty-four, 12-18 months old Hariana heifers were used to determine the effects of organic and inorganic dietary copper (Cu) supplementation on performance, nutrient utilization, blood biochemicals and plasma mineral status. Cu was supplemented (8 mg/kg diet DM) as copper proteinate, copper propionate and copper sulfate (CuSO4. Animals were divided into four treatment groups with 6 animals in each group and were fed basal diet as per NRC (2001) for a period of 120 days. The basal diet contained 8.0 mg of Cu/kg DM. T1 (control) was fed only basal diet with no added copper while in T2: 8 mg/kg DM of copper proteinate; T3: 8 mg/kg DM of copper propionate; T4: 8mg/kg diet CuSO4 was added respectively.The intake, daily gain, feed:gain ratio, BCS and FCR were not affected by Cu supplementation. The TDN intake and ADF digestibility were significantly higher in both the organic Cu supplemented groups. The intake of Cu was significantly higher in Cu supplemented groups. The concentration of plasma ALT, AST enzymes, total cholesterol and total immunoglobulins were not affected by sources of Cu in diet. The antioxidant activity and plasma Cu concentration were significantly higher in Cu supplemented groups, irrespective of sources. Thus, supplementation of 8 mg/kg DM Cu had no beneficial effect on growth performance and blood biochemicals. In conclusion, chelating agents have no effect on bioavailability of copper. Also, the organic copper can be a preferred form to be supplemented for better digestibility in heifers.